Detection of raveling layers of water well by electrical resistivity method and evaluation of the causes of sand making of deep well and it’s confronting approach - Mostafavi, Sayed Abdalreza (Revista de la Universidad del Zulia, 2020)
The collapse and destruction of the wall of drilled wells is one of the challenges of drilling water wells, leading to a shortening and reduction of well irrigation over time. This research has been carried out in an area where most of the drilled wells have faced the problem of sand generation in various dimensions. Many drill holes in Bardaskan City, Khorasan Province, their layers at depths of more than 90 meters, face the challenge of drilling, due to the presence of loam and silty sand, which first requires the drilling of wells at low distances and, secondly, the average life of the wells in these areas is generally less than 8 years and in most cases between 6 and 8 years of age. Furthermore, the problem of cutting or collapsing the tube, especially in the highest part of the first network, is also indirectly correlated with the generation of sand in the wells. The appearance of sand in a well is due to a variety of reasons, although the abundance of very fine-grained loamy and sandy materials is one of the main factors in the aqueous layers of the area. Using the geoelectric and specific resistance method, it is possible to identify layers that have silt and sand with the probability of collapse and determine the point of the layer with less fraying and determine the appropriate strategy to prevent the pipe wall shell from tilt or fill, affecting the well. In this investigation, six wells from the village of Hassan Abad in Bardaskan County, and two wells from the village of Hatiteh have been evaluated, as most of their wells face the problem of wall collapse. Using the geophysical method, the resistance of its canyoning layers has been identified and, by providing engineering solutions, a large amount of damage to the wells has been avoided.